Norway : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes Norway's economy that has a maturing oil and gas industry. Norway's half century of good fortune from its oil and gas wealth may have peaked. Oil and gas production will continue for many decades on current projections, but output and investment have flattened out, and the spillovers from the offshore oil and gas production to the mainland economy may have turned from positive to negative. Thus far, economic policy has needed to focus on managing the windfall, and Norway's institutions have been a model for other countries. Going forward, the challenges are expected to become more complex.